The effect of complex exercises (physical skill) in developing response speed and blocking wall for beach volleyball players - Hafith, Hatem Falih; Rashid, Firas Kassoub (International Journal of Psychosocial Rehabilitation, 2020)
The goal of the research is to prepare complex (physical and skill) exercises for beach volleyball players. Knowing the impact of complex (physical and skill) exercises in developing response speed and blocking for beach volleyball players, as the researchers hypothesized that there was a significant statistically indicated effect of complex (physical and skill) exercises in developing response speed and the blocking wall of the beach volleyball game players. The researchers have used the experimental approach with design of equal groups (experimental and control) on a sample of beach volleyball players for the 2019-2020 season, from the original research community, with (16) players who were divided into two equal groups, the first is experimental, as the number is (8) players, the second is a control, the number is (8) also. After excluding (4) players for the explorantal experience, the homogeneity and parity operations were performed, as well as using the appropriate means, tools and devices for the research procedures and selecting tests for response speed and block wall in the beach volleyball game, after that, the researchers conducted the pre-tests and then applied the complex exercises for a period of (6) weeks with two educational units per week, then conducting the post-tests with the same conditions and cercomstances in which the pre-tests were conducted. After that the results of the research were treated by their own statistical means, through these results several conclusions were reached from them, as special designed combined exercises and followed exercises achieved a positive effect in developing the response time of movement and the skill of the blocking wall in varying proportions. Special designed complex exercises were the best in developing kinematic response time for members of the experimental group of exercises which are used for members of the control group. Special complex designed exercises were the best in developing (blocking wall skill) among members of the experimental group of exercises which used for members of the control group.